Pengaruh Umur Parasitoid Xanthocampoplex sp. (Hymenoptera: Ichneumonidae) terhadap Jumlah Larva Chilo sacchariphagus Bojer (Lepidoptera: Crambidae) di Laboratorium - Sari M. D. Panggabean; Maryani Cyccu Tobing; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2015)
This objective was to study the effect of the ages of Xanthocampoplex sp. on the number of larvaeC. sacchariphagus. The research was held at Laboratory of Sugarcane Research and DevelopmentSei Semayang, Binjai, North Sumatera from November 2013 until January 2014. The method usedRandomized Complete Design with two factors and three replications. The first factor was imago’sage (0, 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10 days) and the second factor was number of host (1, 3, 5 larvaeC. sacchariphagus). All parasitoid larvae appear from C. saccharipaghus was female. The highestpercentage parasitation (35.55%) on age 7 days Xanthocampoplex sp. and the lowest (0.00%) on1, 9, and 10 days Xanthocampoplex sp. The highest number of parasitoid was 1.00 and the lowestwas 0.00 and the highest number of host was 0.70 in number of host was 5 larvaeC. sacchariphagus and the lowest was 0.06 in 1 larvae C. sacchariphagus.Keywords :Xanthocampoplex sp., parasititation, C. sacchariphagus.